AHMAD AMIN: KRITIK DAN PEMIKIRANNYA TENTANG HADIS - Nurmahni Nurmahni (Khatulistiwa, 2011)
Ahmad Amin was a modern muslim scholar that produced critical works in the field of Islamic thought, including critical thinking of Hadith.His critical thinking can be found in his most famous book entitled "Dhuha al-Islam" where he criticized forgery of Hadith due to the lack of a written record of Hadith from the beginning. The interpretation of the critical analysis of Ahmad Amin requires extensive a critical approachinvolving many aspects including historical aspects in it.